World Scientific Production in Psychology - García Martínez, Ana Teresa; Universidad de Extremadura, España (2012)
This study examines world scientific production in Psychology based on bibliometric indicators (scientific production, production’s percentage variation, average citations per document, normalized citation, impact, etc.), for the period 2003–2008. The analysis is made by country, by research institutions, and scientific journals, using the Scopus (Elsevier), database of scientific literature. The results show that total world production has increased over the period studied. Four groups are acknowledge for each country, institutions, and journals, taking into account their values of scientific production, normalized citation, and subject specialization